Solitary and Synergistic Effects of Different Hydrophilic and Hydrophobic Phospholipid Moieties on Rat Behaviors - Shuhei Kikuchi; Yugo Iwasaki; Mina Yoshioka; Kodai Hino; Shin-ya Morita; Ryu Tada; Yasuhiro Uchimura; Yoshinori Kubo; Tomoya Kobayashi; Yusuke Kinoshita; Masahiro Hayashi; Yoshio Furusho; et al. (MDPI AG, 2024)
Glycerophospholipids have hydrophobic and hydrophilic moieties. Previous studies suggest that phospholipids with different moieties have different effects on rodent behavior; however, the relationship between chemical structures and behavioral effects remains unclear. To clarify the functions of phospholipid moieties, we injected male rats with phospholipids with different moieties and conducted behavioral tests. Exploratory activity was reduced by phosphatidylethanolamine (PE)(18:0/22:6) but not PE(18:0/18:0) or PE(18:0/20:4). Conversely, exploratory activity was increased by plasmanyl PE(16:0/22:6), which harbors an alkyl-ether linkage, but not by phosphatidylcholine (PC)(16:0/22:6) or plasmanyl PC(16:0/22:6). Docosahexaenoic acid (DHA)(22:6) and an alkyl-ether linkage in PE were thus postulated to be involved in exploratory activity. Anxiety-like behavior was reduced by plasmenyl PC(18:0/20:4), which harbors a vinyl-ether linkage, but not by PC(18:0/20:4) or plasmanyl PC(18:0/20:4), suggesting the anxiolytic effects of vinyl-ether linkage. The activation of social interaction was suppressed by PE(18:0/18:0), PE(18:0/22:6), PC(16:0/22:6), plasmanyl PE(16:0/22:6), and plasmanyl PC(16:0/22:6) but not by PE(18:0/20:4), plasmenyl PE(18:0/20:4), or plasmanyl PC(18:0/22:6). DHA may suppress social interaction, whereas arachidonic acid(20:4) or a combination of alkyl-ether linkage and stearic acid(18:0) may restore social deficits. Our findings indicate the characteristic effects of different phospholipid moieties on rat behavior, and may help to elucidate patterns between chemical structures and their effects.